2017
DOI: 10.1177/2042018817742580
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of glycemic markers HbA1c, 1,5-anhydroglucitol and glycated albumin in evaluating gestational diabetes mellitus

Abstract: HbA1c and 1,5-AG alone does not have sufficient diagnostic accuracy to diagnose GDM. 1,5-AG values were correlated with post-load glucose values in pregnant women so will improve the GDM management and be useful to predict complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
2
5
2
Order By: Relevance
“…Zhu et al [22] reported that the AUC values were 0.726 for FPG and only 0.542 for GlyA in the second trimester. Similar observation was made by Saglam et al [25], with the AUC of GlyA being 0.550 in the GDM diagnosis. In our study, we also found a higher diagnostic value of FPG (AUC = 0.721) than that of GlyA (AUC = 0.509) during the 24-28 weeks of gestation.…”
Section: Discussionsupporting
confidence: 88%
“…Zhu et al [22] reported that the AUC values were 0.726 for FPG and only 0.542 for GlyA in the second trimester. Similar observation was made by Saglam et al [25], with the AUC of GlyA being 0.550 in the GDM diagnosis. In our study, we also found a higher diagnostic value of FPG (AUC = 0.721) than that of GlyA (AUC = 0.509) during the 24-28 weeks of gestation.…”
Section: Discussionsupporting
confidence: 88%
“…It was shown that 1,5‐AG is more sensitive to reflect postprandial blood glucose than HbA1c and glycated albumin, and to detect glucose fluctuation in the shorter term. In some recent studies, 1,5‐AG was used as a screening tool for type 2 diabetes and gestational diabetes mellitus. Unfortunately, in the present study, in group D, which showed significant changes in the proportions of patients achieving HbA1c <7%, 1,5‐AG levels did not increase synchronously.…”
Section: Discussioncontrasting
confidence: 76%
“…Zhu et al [20] reported that the AUC values were 0.726 for FPG and only 0.542 for GA in the second trimester. Similarly, observation was made by Saglam et al [23] with the AUC of GA being 0.550 in the GDM diagnosis. In our study, we also found a higher diagnostic value of FPG (AUC = 0.705) than that of GA (AUC = 0.503) during the 24-28 weeks of gestation.…”
Section: Discussionsupporting
confidence: 71%